Electrical activation to the parasternal intercostal muscles during high-frequency spinal cord stimulation in dogs - DiMarco, Anthony F. (J Appl Physiol (1985), 2014)
High-frequency spinal cord stimulation (HF-SCS) is a novel technique of inspiratory muscle activation involving stimulation of spinal cord pathways, which may have application as a method to provide inspiratory muscle pacing in ventilator-dependent patients with spinal cord injury. The purpose of the present study was to compare the spatial distribution of motor drive to the parasternal intercostal muscles during spontaneous breathing with that occurring during HF-SCS. In nine anesthetized dogs, HF-SCS was applied at the T2 spinal level. Fine-wire recording electrodes were used to assess single motor unit (SMU) pattern of activation in the medial bundles of the 2nd and 4th and lateral bundles of the 2nd interspaces during spontaneous breathing and HF-SCS following C1 spinal section. Stimulus amplitude during HF-SCS was adjusted such that inspired volumes matched that occurring during spontaneous breathing (protocol 1). During HF-SCS mean peak SMU firing frequency was highest in the medial bundles of the 2nd interspace (17.1 ± 0.6 Hz) and significantly lower in the lateral bundles of the 2nd interspace (13.5 ± 0.5 Hz) and medial bundles of the 4th (15.2 ± 0.7 Hz) (P < 0.05 for each comparison). Similar rostrocaudal and mediolateral gradients of activity were observed during spontaneous breathing prior to C1 section. Since rib cage movement was greater and peak discharge frequencies of the SMUs higher during HF-SCS compared with spontaneous breathing, stimulus amplitude during HF-SCS was adjusted such that rib cage movement matched that occurring during spontaneous breathing (protocol 2). Under this protocol, mean peak SMU frequencies and rostrocaudal and mediolateral gradients of activity during HF-SCS were not significantly different compared with spontaneous breathing. This study demonstrates that 1) the topographic pattern of electrical activation of the parasternal intercostal muscles during HF-SCS is similar to that occurring during spontaneous breathing, and 2) differential spatial distribution of parasternal intercostal activation does not depend upon differential descending synaptic input from supraspinal centers.